Pengaruh Gaya Mengajar Komando Terhadap Hasil Belajar Tolak Peluru Gaya Menyamping Pada Siswa SMA - Edita A.M. Pinangkaan (Peneliti.net, 2022)
This study aims to examine the application of the commando teaching style on the learning outcomes of sideways style sweating at the high school students of State I Kawangkoaan. The method used in this research is the experimental method. The sample used was the students of the State High School I Kawangkoaan, totaling 20 samples, which were divided into two groups, namely the experimental group with a command teaching style totaling 10 samples and the control group receiving no treatment totaling 10 samples. The instrument used in this study was a